Pengaruh Pelatihan Kerja dan Stres Kerja Terhadap Produktivitas Karyawan PT Maelsov Mega Teknologi - Jeus Sitha Riadi Putra; Siti Nurjanah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of job training and job stress on employee productivity. This study uses a quantitative approach. This research was conducted with the analysis unit of PT Maelsov Mega Teknologi with a population of 44 employees. The sampling method used is Non-Probability sampling with a saturated sampling technique taken as many as 44 respondents, with data collection carried out by distributing questionnaires using a Likert scale to measure each statement. Data processing method using validity test, reliability test, multiple linear regression, T test, F test and Rsquare coefficient test with the help of SPSS 20 program. The results show that there is a significant effect of training on productivity, there is a significant effect of work stress on productivity and also Simultaneously training and job stress have a positive and significant impact on the productivity of PT Maelsov Mega Teknologi's employees.